STRATEGI BISNIS DALAM MENINGKATKAN KEUNGGULAN BERSAING PADA PT. BALI EXOTIC WEDDING - F. Mateus L. Osorio Soares (Universitas Pendidikan Nasional, 2014)
The business strategy is the policy and guidelines set out how a company competes inan industry, and in particular, the foundation base where he's trying to build a competitiveadvantage.Informants in this study is that leadership as well as the owner of PT. Bali ExoticWedding to get a picture of the business strategy undertaken by PT. Bali Exotic Wedding toachieve competitive advantage and several employees of PT. Bali Exotic Wedding-related inorder to obtain an overview of the barriers and drivers of which is owned by PT. Bali ExoticWedding and to identify the strengths, weaknesses, opportunities, and threats to the PT. BaliExotic Wedding SWOT analysis technique used.The results showed that the right business strategy implemented by PT. Bali ExoticWedding is: (1) cost advantage strategy (cost leadership). (2) Product DifferentiationStrategies / Differentiation (differentiation). (3) The strategy focus. (4) Image StrategyKeywords: Business Strategy, competitive advantage.